Taxonomical, Phytochemical and Pharmacological Reviews of Musa sapientum var. Paradisiaca. - Mahadeva Rao, U.S; Khamsah Suryati, Mohd; Mohaslinda, M.; Rosmawati, Mat Ali (2014)
The use of plants as medicine has been referred to since ancient peoples, perhaps as early as Neanderthal man. Plants are a source of many biologically active products and nowadays they are of great interest to the pharmaceutical industry. The study of how people of different culture use plants in particular ways has led to the discovery of important new medicines. Bananas and plantains (Musa spp.) are grown extensively throughout the tropical and subtropical regions of the world. The terms ‘bananas’ and ‘plantains’ require clarification. ‘Bananas’ refers to all the members of the genus Musa. In the narrow sense, plantains are characterized by the orange-yellow color of both the compound tepal of the flower and the fruit pulp at ripeness. In this review work, we discuss the possible activity of Musa paradisiaca L. and M. sapientum (Musaceae) for their anti-diabetic activity, antiulcer activity, antioxidant property, wound healing, hair growth promoter, diuretic, analgesic, augmenting action on skeletal muscle contraction,antihypertensive activity, anti-allergic activity and mutagenic effects and haemostatic activity. This literature review also presents some taxonomy, traditional uses, phytochemicals, minerals and detailed pharmacological information of Musa paradisiaca var. sapientum Linn. Some pharmacological studies has been reported and number of activities require the proper scientific justification on the plant in which diarrhoea, dysentery, ulcer, antispasmodic, hypertension, nephroprotective activity and cardiac diseases etc., are scientifically possible. The different phytoconstituents present in the unripe fruit extract of the plant like; alkaloids, steroids, glycosides, flavonoids etc that gives the possibility of expected pharmacological activities and which help for further research and treatment for the patients.